Book lovers - Henry, Emily (New York : Jove, 2022)
Agreeing to a holiday escape to the country, literary agent Nora keeps running into a bookish, hardheaded, arrogant editor she knows from Manhattan, and wishes she didn$1 (Bt, even as she discovers they have more in common than previously thought.s
Includes a Reader's Guide and Discussion Questions plus Nora and Libby's Ultimate Reading List.
Keywords: Literary agents -- Fiction; Editors -- Fiction; Summer -- Fiction; Vacations -- Fiction; Man-woman relationships -- Fiction; Sisters -- Fiction; North Carolina -- Fiction; Romance fiction